Validitas dan Reliabilitas Ujian SOCA (Students Oral Case Analysis): Studi di Salah Satu Fakultas Kedokteran di Indonesia - Rizka Aries Putranti; Ova Emilia; Efrayim Suryadi (Jurnal Pendidikan Kedokteran Indonesia, 2016)
Background: Medical faculty has to make sure that the students meet the minimal competence needed using apropriate exam. While the exam itself should facilitate students to learn. Oral examination has known for its ability to facilitate students learn but low in validity and reliability. Medical faculty of Lampung University (FK Unila) apply the student oral case analysis (SOCA) exam as one of block assessment component, as with MCQ, tutorial, and laboratory exam. This study aimed to evaluate validity and reliability of SOCA examination at FK Unila